An icaritin-loaded microemulsion based on coix oil for improved pharmacokinetics and enhanced antitumor efficacy. (31st December 2022) - Zeng, Huating; Li, Xiaoqi; Liu, Yuping; Li, Xia; Qu, Ding; Chen, Yan
Abstract: Combinational icaritin (IC) and coix seed oil (CSO) holds promising potential in the treatment of hepatocellular carcinoma. However, traditional cocktail therapy is facing difficulties to optimize the synergistic antitumor efficacy due to the asynchronous pharmacokinetics. Therefore, we developed an icaritin-loaded microemulsion based on coix seed oil (IC-MEs) for improved pharmacokinetics and enhanced antitumor efficacy. The preparation technology of IC-MEs was optimized by the Box–Behnken design and the pharmaceutical properties were characterized in detail. IC-MEs show synergistic antiproliferation against HepG2 cells compared with monotherapy. The mechanism is associated with stronger apoptosis induction via enhancing caspases-3 activity. IC-MEs significantly improve the bioavailability of IC due to the encapsulation of coix oil-based microemulsion and also obtain the desired liver accumulation and elimination. More importantly, IC-MEs exhibit the overwhelming antitumor ability among all of the treatments on the HepG2 xenograft-bearing mice. This study verifies the feasibility of using coix oil-based microemulsion to improve the antitumor effect of water-insoluble components.